ANALISIS PERBANDINGAN KINERJA KEUANGAN PERUSAHAAN SEBELUM DAN SESUDAH MELAKUKAN AKUISISI : COMPARATIVE ANALYSIS OF THE FINANCIAL PERFORMANCE OF COMPANIES LISTED ON THE IDX BEFORE AND AFTER ACQUISITIONS - Zumarnis, Hafizah; Andriani, Sonja (CURRENT: Jurnal Kajian Akuntansi dan Bisnis Terkini, 2023)
This study aims to analyze the comparative financial performance of companies listed on the Indonesia Stock Exchange (IDX) that made acquisitions in 2019, two years before and two years after the acquisition. Performance comparison are measured using financial ratios, including ROA, TATO, and DER. This research is quantitative research with sampling techniques using purposive sampling techniques. The data analysis method uses descriptive statistical analysis, data normality test, and paired sample t-test hypothesis testing. Based on the results of research on the entire company, it shows that the ROA, TATO, and DER ratios have no significant difference between before and after the acquisition. The results of this study are used so that companies can pay more attention to the condition of their financial performance between before and after the acquisition so that the company can achieve the expected acquisition objectives, namely generating better synergies in the future. In addition, this financial performance measurement can provide a source of information for investors, related to the condition of the company's financial performance between before and after the acquisition, so that it can provide a consideration for investors when investing in companies that make acquisitions.